FISH DIVERSITY IN THE TESSO NILO AREA, RIAU WITH NOTES ON RARE, CRYPTIC SPECIES - Ike Rachmatika; A. Munim; G. W. Dewantoro (Treubia, 2006)
A survey of the freshwater fishes of The Tesso Nillo area was conductedin June 2003 in conjunction of establishing this area as conservation area. In this brown water-forest streams of the upper part of Kampar catchment area, fifty fish species were found. This comprised of 31 genera, 16 familia and 4 orders. The dominant familia are Cyprinidae (18 species), Bagridae (5 species), Belontiidae (4 species) and Siluridae (4 species). Cryptic species: Breinsteinea hypselurus and Chaca bankanensis were found in the area.